Pengaruh Penyalahgunaan Teknologi Informasi dan Pemahaman Ajaran Tamansiswa Tri Pantangan terhadap Perilaku Kecurangan Akademik Mahasiswa Akuntansi - Wardani, Dewi Kusuma; Andini, Sella Putri (Universitas Pamulang, 2022)
Looking at the current situation, fraudulent behavior commited by accountants and accounting student as prospective accountants still occurs frequently. This study aims to examine the effect of misuse of information technology and understanding of tamansiswa tri pantangan teachings on academic fraud behavior of accounting students as prospectives accountant.. The research method used is quantitative. The sample in this study was obtained from accounting students from the 2019-2021 batch at Sarjanawiyata Tamansiswa University, using the convenience sampling method. The number of samples used were 114 respondents. Data analysis in this study used multiple regression analysis. The results of the study show that misuse of information technology has a positive effect on academic fraud behavior. Meanwhile, understanding of the teachings of tamansiswa tri pantangan have a negative effect on academic cheating behavior. The research is used for consideration for student and universities in responding to cases of academic fraud in order to maintain the quality of academic learning. The results of this study are expected to provide information for universities so that they can evaluate regulations or policies regarding academic cheating. Strictly speaking, regulations can reduce the level of academic fraud so that in the future there will be no more cases of academic fraud in tertiary institutions